Konsep Hak Cipta Sebagai Jaminan Fidusia Menurut Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta dan Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia Dalam Rangka Mewujudkan Kepastian Hukum - Taryan Setiawan (Jurnal Media Justitia Nusantara, 2018)
The development of copyright contained in Law No. 28 of 2014 concerning Copyright provides legal protection for the creation of copyrighted works. In addition, the Copyright Law has a provision that copyright can also be used as an object of fiduciary guarantee. This shows that copyright is currently very useful for holders of copyrighted works because their creation can be used as collateral to get debt in a fiduciary manner. The practice of Law No. 42 of 1999 concerning Fiduciary which is a legal umbrella for parties in carrying out fiduciary practices has not fully accommodated the implementation of copyright as a fiduciary guarantee, therefore it is necessary to do research on how the concept of copyright regulation can create legal certainty ? and how can the concept of copyright execution as the object of fiduciary collateral in implementing the law on fiduciary be able to bring about legal certainty? The research carried out was descriptive, namely describing the symptoms in the community towards a case to be studied, the approach taken was a qualitative approach which was the method of research that produced descriptive data. The types and sources of legal material in this study use the Civil Code, Trade Criminal Code, Law Number 28 of 2014 concerning Copyright and Law Number 42 of 1999 concerning Fiduciary Guarantees, Bank Indonesia Regulation Number 9/6 / PBI / 2007 as legal material primary, expert theories as secondary legal material. This legal research uses data collection techniques by studying documents or library materials from both print and electronic media (internet). The data obtained will be analyzed descriptively. The results of the study found that some of the reasons for this were the lack of socialization regarding the provisions so that copyright holders did not know it, the reluctance of banks or other guarantee institutions to accept copyright as an object of fiduciary guarantee because the implementation rules of the provision were unclear, and the existence provisions in Bank Indonesia Regulation (PBI) Number 9/6 / PBI / 2007 which regulate limitatively about movable objects which can be used as fiduciary guarantees while copyrights are not listed as one of them, so banks are hesitant to accept copyright as fiduciary guarantee, while banks or other guarantee institutions certainly hold the principle of prudence in providing credit loans.